Hypotensive and vasorelaxant effect of Diapocynin in normotensive rats - Potje, Simone R. [UNESP]; Troiano, Jéssica A. [UNESP]; Graton, Murilo E. [UNESP]; Ximenes, Valdecir F. [UNESP]; Nakamune, Ana Claúdia M.S. [UNESP]; Antoniali, Cristina [UNESP] (Elsevier, 2017)
Nicotinamide adenine dinucleotide phosphate oxidase (NAD(P)H-oxidase) is a multicomponent enzyme system that generates superoxide anion by one-electron reduction of molecular oxygen and represents the major source of reactive oxygen species (ROS) in the vascular cells. Apocynin has been extensively used as an inhibitor of NADPH oxidase (NOX) in phagocytic cells and as an antioxidant in non-phagocytic cells. In phagocytes cells, due to the presence of myeloperoxidase, apocynin can be the converted to diapocynin, which is supposed to be the active form of this phytochemical. Moreover, apocynin was shown to induce hypotension and vasodilatation in many experimental animal models. However, there are no studies showing the effects of diapocynin on blood pressure or in vascular cells. In this present study, we used chemically synthesized diapocynin and analyzed its antioxidant capacity, effect on blood pressure and vascular reactivity. Moreover, it was evaluated the levels of nitric oxide (NO), ROS and calcium in aortic endothelial cells stimulated by diapocynin. All results were compared to apocynin. We found that diapocynin showed higher antioxidant capacity than apocynin. Apocynin and diapocynin, promoted hypotensive effects without changing the heart rate, however the effects of diapocynin were reversed faster than the effects of apocynin, which was long lasting. Diapocynin and apocynin induced endothelium dependent and independent vasodilatation, but diapocynin was less potent than apocynin regarding the capacity of induction of vasodilatation in mesenteric resistance arteries and aorta from Wistar rats. The relaxation induced by apocynin or diapocynin involves sGC and potassium channels in vascular smooth muscle cells and NOS participates of relaxation induced by apocynin or diapocynin in intact mesenteric rings. Apocynin and diapocynin increased NO and decreased ROS levels in endothelial cells, however diapocynin did not alter calcium levels in these cells. In conclusion, these results demonstrated that, similarly to apocynin, diapocynin also induces hypotensive and vasodilator effects in rats and vascular endothelium improves the diapocynin vasodilator effects by increases NO bioavailability.
Keywords: Apocynin; Diapocynin; Hypotension; Vasodilatation